Study on Supporting Structure Performance of Deep Soft Soil Foundation Pit near Sea under Waves, Tides, Vibration, and Unbalanced Loads - Junsheng Chen; Chen Lin; Shuzhuo Liu; Haihong Mo (Advances in Civil Engineering)
In addition to the vibration loads caused by offshore structure construction, the offshore foundation pit can also be affected by additional hydraulic loads such as waves, tides, and typhoons, hindering our understanding of the mechanical performance of the foundation pit supporting structure. In order to illuminate this mechanical performance under waves, tides, hammering, and unbalanced loads, this paper analyzed the supporting structure with theoretical and numerical simulations. The results were verified with field monitoring data. Moreover, the influences of loads, including construction vibration loads and unbalanced loads, on structure and soil were discussed. By applying these results to the engineering design, this research could provide a reference for studying mechanical properties of relevant supporting structures and the construction of offshore foundation pits.